A Lesson from Vernacular Architecture in Nigeria - Joyce Lodson; John Emmanuel Ogbeba; Ugochukwu Kenechi Elinwa (Alanya Hamdullah Emin Paşa Üniversitesi, 2018)
Contemporary architecture has its roots from the vernacular. Every cultural group in the world has its own form of vernacular though the approach may vary from place to place and from people to people. Vernacular architecture has many values which are relevant to contemporary architecture today. This paper looks at vernacular architecture in Nigeria as practised by two ethnic groups who have varying climatic, religious and socio-cultural practices. The approaches to architecture by these two groups, i.e. the Hausas and Igbos, are looked at with the intention of finding positive values in the vernacular which can be applied to the contemporary. One of such values as seen in this paper is the harmony of traditional building materials with nature. Local building materials are able to meet housing needs without having a detrimental effect on the environment. More emphasis should therefore be given to local building materials in the building industry today. The paper concludes by stating that for contemporary architecture to adequately meet the needs of man today, vernacular values which apply to the cultural and climatic needs of such places should be selected and imbibed.